Symbol

# Calculator search results

Formula
Solve the equation
Graph
$2 x + y = 7$
$x$Intercept
$\left ( \dfrac { 7 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , 7 \right )$
$2x+y = 7$
$x = - \dfrac { 1 } { 2 } y + \dfrac { 7 } { 2 }$
 Solve a solution to $x$
$2 x \color{#FF6800}{ + } \color{#FF6800}{ y } = 7$
 Move the rest of the expression except $x$ term to the right side and replace the sign 
$2 x = 7 \color{#FF6800}{ - } \color{#FF6800}{ y }$
$2 x = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \color{#FF6800}{ y }$
 Organize the expression 
$2 x = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 7 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 7 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
$x = \left ( \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
 Convert division to multiplication 
$x = \left ( \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$x = \left ( \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
 Multiply each term in parentheses by $\dfrac { 1 } { 2 }$
$x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$x = - \dfrac { 1 } { 2 } y + \color{#FF6800}{ 7 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
 Calculate the product of rational numbers 
$x = - \dfrac { 1 } { 2 } y + \color{#FF6800}{ \dfrac { 7 } { 2 } }$
$y = - 2 x + 7$
 Solve a solution to $y$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } + y = 7$
 Move the rest of the expression except $y$ term to the right side and replace the sign 
$y = 7 \color{#FF6800}{ - } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \right )$
$y = \color{#FF6800}{ 7 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \right )$
 Organize the expression 
$y = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 7 }$
Solution search results
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture